Contents Standard Policy of Basic Education in The National Level Reviewed from The Scope of Citizenship Education Materials - I Gusti Ngurah Santika; Ida Bagus Putu Arnyana; I Wayan Suastra; I Made Kartika (Journal of Sustainable Development Science, 2022)
In essence, education in the context of national development has an instrumental role and function, namely as a unifying nation, equalizing opportunities, and developing self-potential. The purpose of this study was to determine the national level policy on the content of national education standards in terms of the scope of Citizenship Education material. This research used library research as the research method. The results of this research indicated that content standards serve as guidelines/references/signs for teachers when providing material in learning activities. Scope of Material for Elementary School/Madrasah Ibtidaiyah/Extraordinary Elementary School/Package A/Other Equal Forms, such as applicable norms and rules, deliberation, characteristics of the family environment, and the importance of maintaining togetherness as capital in upholding unity and integrity and form of attitude and behavior to maintain unity and integrity in the school environment, and the community. Scope of Materials for Junior High Schools/Madrasah Tsanawiyah/Extraordinary Junior High Schools/Package B/Other Equal Forms, such as the chronology of changes to the 1945 Constitution of the Republic of Indonesia as a written basic law, as well as the constitution of the Indonesian state, diagrams of governance linkages the sequence of laws in force in Indonesia, the embodiment of democracy based on the values ​​of Pancasila in the Indonesian government system, the Territory of the Unitary State of the Republic of Indonesia, and the form of state, form of government, and system of government.